Factors of Entrepreneurs on Choosing Culinary-based Business - Kurniawan, Indra; Rachmawati Chaldun, Evy (Journal of Innovation, Business and Entrepreneurship, 2018)
Abstract. Entrepreneurship is the important activity for economic growth of the country. One actor of entrepreneurship activity called an entrepreneur. There is still a low number of the entrepreneur in Indonesia with 3,1% in 2016 rather than other Asian countries such as Malaysia, Singapore, and China which has more than 5%. But, that is increasing than years before and it indicates that being an entrepreneur is attractive. Many entrepreneurs running a culinary business which it has contributed one of the biggest GDP (Gross Domestic Product) for Indonesian economic with 41,69% in 2015. The government also support those entrepreneurs and wanted to generate new entrepreneurs in Indonesia and Bandung as one of the cities of the culinary destination. Become an entrepreneur and choosing culinary as the business itself consists of several influence factors. In the process, there is also a failure although barrier of entry in culinary business especially in Indonesia is low. It makes factors influencing entrepreneur on choosing culinary business becomes important to know. This research conducted by using a qualitative method with phenomenological study used and gather the data with purposeful sampling from 10 culinary business entrepreneur in Bandung by using the semi-structured interview. The result analyzes with coding based on the interview result. The result has shown that the most important factor is Opportunity-based with Entrepreneurial Alertness as the category in approaching the opportunity. There are also other factors that influence them in the findings which are Passion, Development Needs, Greater Business Achievement, and Economic Needs. The result can be used for evaluating the business activity and reflection for entrepreneurs that wanted to choose culinary as the business to do.Keywords: Choosing Culinary Business, Culinary Business, Entrepreneurs, Entrepreneurship, Influencing Factors